2020
DOI: 10.1371/journal.pone.0230198
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of proposed substrate-binding residues of Hsp104

Abstract: Hsp104 is a hexameric AAA+ yeast disaggregase capable of solubilizing disordered aggregates and amyloid. Hsp104 couples ATP hydrolysis to polypeptide translocation through its central channel. Substrate binding by Hsp104 is mediated primarily by two conserved tyrosine residues in nucleotide binding domain (NBD) 1 and NBD2. Recent structural studies have revealed that an additional tyrosine residue (Y650) located in NBD2 appears to contact substrate and may play an important role in Hsp104 function. Here, we fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…An R417A mutation ablated PARL Skd3 disaggregase activity but had no effect on ATPase activity, indicating a critical role for this arginine. By contrast, mutations in the secondary pore loops of Hsp104 and ClpB have much milder effects on disaggregase activity (Howard et al, 2020; Rizo et al, 2019). Thus, the secondary pore loop of PARL Skd3 plays a more important role in disaggregase activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An R417A mutation ablated PARL Skd3 disaggregase activity but had no effect on ATPase activity, indicating a critical role for this arginine. By contrast, mutations in the secondary pore loops of Hsp104 and ClpB have much milder effects on disaggregase activity (Howard et al, 2020; Rizo et al, 2019). Thus, the secondary pore loop of PARL Skd3 plays a more important role in disaggregase activity.…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the role of the secondary pore loop, we generated PARLSkd3 R417A , which exhibited similar ATPase activity to PARLSkd3 (Figure 2C), but diminished disaggregase activity (Figure 2D). This loss of function is substantially more severe than that caused by equivalent mutations in ClpB or Hsp104 (Howard et al, 2020;Rizo et al, 2019). Thus, the secondary pore loops play a more critical role in PARLSkd3 disaggregase activity than in Hsp104 or ClpB.…”
Section: Substrate Contacts and Nbd Occupancy Support A Conserved Ste...mentioning
confidence: 97%
“…While many studies have probed the basis for Hsp104 potentiation, the specific mechanistic drivers that enhance Hsp104 activity have remained confounding. 8,9,12,13,24,27,28,30 Structural, genetic, and biochemical studies have suggested that the coiled-coil MD is an autoinhibitory domain, whereby potentiation can be conferred by breaking both intra-and inter-molecular MD-MD contacts, as well as contacts between the MD and NBD1. 12,16,28,31 Studies linking potentiation to more specific structural changes have been challenging, which is likely due to the highly dynamic nature of the MD, which is typically poorly resolved in otherwise high resolution cryo-EM structures.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have probed the basis for Hsp104 potentiation, the specific mechanistic drivers that enhance Hsp104 activity have remained confounding 8,9,12,13,24,27,28,30 . Structural, genetic, and biochemical studies have suggested that the coiled‐coil MD is an autoinhibitory domain, whereby potentiation can be conferred by breaking both intra‐ and inter‐molecular MD‐MD contacts, as well as contacts between the MD and NBD1 12,16,28,31 .…”
Section: Introductionmentioning
confidence: 99%
“…The PQC system comprising a sophisticated network of proteins, called the chaperones, is not only devoted to the proper folding of nascent polypeptide chains but also guides the unfolded and misfolded proteins to attain the native three-dimensional shape by inhibiting their aberrant aggregation and eliminating irreversibly aggregated proteins ( 10 , 11 , 12 ). Disaggregases (Hsp110 in higher eukaryotes; ClpB in Escherichia coli ; Hsp104 in yeast) belong to an important class of chaperones that are involved in the ATP-dependent and cochaperone-regulated disassembly of aggregated proteins that bypass the other surveillance of the PQC system ( 13 , 14 , 15 , 16 , 17 ). In aged neurons, however, one of the critical manifestations of the PQC dysfunction is the lower expression of these disaggregases such as Hsp110, Hsp70, and so forth ( 18 ).…”
mentioning
confidence: 99%